Overview of Germ Patterns and Sensitivity of Bacteria Causing Urinary Tract Infections in Westerindo Laboratory - Nurrus Samsiah, Widiya; Didik Prasetya; Moh.Fairuz Abadi (CV. CENDIKIA JENIUS INDONESIA, 2025)
Urinary tract infection (UTI) is a global health problem with high incidence and dynamic bacterial resistance patterns, requiring regular monitoring to ensure appropriate therapy. Irrational antibiotic use may worsen resistance. This study aimed to determine the bacterial patterns and antibiotic sensitivity of UTI pathogens at Westerindo Laboratory in 2023. A retrospective descriptive design with total sampling was applied to 137 patients who underwent urine culture from January to December 2023. Secondary data were obtained from the laboratory information system and analyzed using WHONET. Bacterial identification was performed through culture on Mac Conkey and blood agar, Gram staining, and Vitex 2 testing. Results showed that most respondents were female (55.47%). Of the 18 bacterial species identified, 83.3% were Gram-negative, with Escherichia coli as the predominant pathogen (30.65%), followed by Klebsiella pneumoniae (16.05%), Proteus mirabilis, and Morganella morganii (12.40%). Sensitivity testing of 327 antibiotics revealed 68.5% with high sensitivity, while Meropenem and Tigecycline showed 100% effectiveness against E. coli. Sixteen Extended Spectrum Beta Lactamase (ESBL) isolates were identified. In conclusion, UTIs were mainly caused by Gram-negative bacteria, particularly E. coli, with antibiotic resistance remaining a serious issue. Recommended Local antibiogram data, resistance monitoring, and antimicrobial stewardship are strongly recommended.